2006
DOI: 10.2527/jas.2005-663
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte fatty-acid binding protein is closely associated to the porcine FAT1 locus on chromosome 41

Abstract: We identified 22 polymorphisms in the adipocyte fatty-acid binding protein (FABP4) gene, a strong positional candidate gene for the FAT1 locus in porcine chromosome 4. The most informative polymorphism, an insertion/deletion in intron 1, together with a single nucleotide polymorphism in intron 3, was genotyped in a cross between Iberian and Landrace pigs. After performing QTL, single marker, and haplotype analyses, we showed that there were at least 2 quantitative trait genes in the FAT1 region and that the FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…However, on the basis of Hirschhorn and Altshuler's review (13), in the case of putative results such as in this study, replication is paramount, because prior probabilities of true association are low and thus, all genetic associations demand a high level of proof. Recently several research groups reported association of FABP4 polymorphisms with back fat traits in pigs (14,15). Our result also indicated the BF association with bovine FABP4 polymorphisms.…”
Section: Resultssupporting
confidence: 75%
“…However, on the basis of Hirschhorn and Altshuler's review (13), in the case of putative results such as in this study, replication is paramount, because prior probabilities of true association are low and thus, all genetic associations demand a high level of proof. Recently several research groups reported association of FABP4 polymorphisms with back fat traits in pigs (14,15). Our result also indicated the BF association with bovine FABP4 polymorphisms.…”
Section: Resultssupporting
confidence: 75%
“…These results could be due to the following reasons: (1) other mutations occurred within 3' or 5' flanking regulatory regions and these mutations have not been detected yet; (2) the SNP indirectly affected meat quality traits by being in linkage disequilibrium with another polymorphism that directly influenced the quantitative traits. This hypothesis is supported by the following facts: the porcine FABP4 is closely associated to the FAT1 locus on chromosome 4, and the FAT1 has an important effect on meat marbling and growth (Mercadé et al, 2006). Furthermore, integrated analyses of both genetic map and radiation hybrid (RH) map indicated that the bovine FABP4 gene falls into the QTL interval for marbling on chromosome 14 (Michal et al, 2006).…”
Section: Discussionsupporting
confidence: 56%
“…There are many papers concerned with FABP4 as a candidate gene for fat traits of meat quality in pigs, and FABP4 shows high nucleotide variability (Nechtelberger et al, 2001;Mercadé et al, 2006;Ojeda et al, 2006). A mutation of the sheep FABP4 gene, which is located in intron 1 at nt 209 was associated with meat quality traits in our study.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Gerbens et al (1998) reported that polymorphism of microsatellite sequence in intron 1 of the FABP4 was associated with fatness traits in a Duroc population, but studies on other pig breeds did not confi rm this observation (Nechtelberger et al, 2001;Chmurzyńska et al, 2004). Moreover, Mercade et al (2006) suggested that the InDel polymorphism in the fi rst intron (position 2653) is tightly associated with fatness traits. SNPs in the promoter region and in intron 2 of the FABP3 gene were analysed by Gerbens et al (1999) who detected signifi cant associations between three polymorphisms (one in the promoter region and two in the second intron) and fatness traits.…”
Section: Discussionmentioning
confidence: 97%